The effect of farm credit and farm produce in Kano State Nigeria - Mohammed, Ahmed Ibrahim; Aziz, Ahmad Bashir; Ogunbado, Ahamad Faosiy (2017)
Farm produce serves as a sustainable way of livelihood in terms of food security, employment, income, industries and market among others.This paper is a conceptual paper that seeks to explore the viability of Murabahah finance on the relationship between farm credit and farm produce. This is a cross-sectional research design.Method of data collection is questionnaire; a total of 760 individual farmers will be the target respondent in this study.And structural equation model (Smart- PLS 2.0) statistical application will be used for data analysis.It was found that the problems of high interest rate, insufficient and timely farm credit, poor modern farm equipment such as: tractors, harvesters, planters, storage facilities, fertilizer, herbicide, insecticide, transportation and communications among others. Based on these findings appropriate recommendations were suggested that will tackle the affirmation problems.